Between Ritual and Local Tradition: A Study on The Meaning of The Rebo Wekasan Annual Event in Desa Tugu Selatan - Muhammad Zendi Alfarizi; Clarisa Ramadanti Ridho Kusumo; Anissa Febryani; alawiyah, siti tuti (Universitas Nasional, 2025)
This research article aims to identify the implementation of Rebo Wekasan and explain the meaning of the Rebo Wekasan tradition for the society of Tugu Selatan Village, Cisarua District, Bogor Regency, West Java Province. The method used was qualitative. The data was collected by using interviews and Palmer's (1996) cultural semantic approach with four aspects of meaning, namely sense, feeling, tone, and intention, in the data analysis process. The informants who were involved included the society, religious leaders, and the Rebo Wekasan event committee of Desa Tugu Selatan. The results show that in terms of sense, Rebo Wekasan is interpreted as an economic innovation to support MSMEs, a symbol of gratitude and mutual cooperation, and a form of togetherness. In terms of feeling, the villagers feel happy because they can strengthen their friendship. The tone aspect is reflected in the friendly, intimate, communicative and religious atmosphere during the event. In terms of intention, this activity aims to preserve customs, strengthen relationships and solidarity, and provide cultural education for future generations. Thus, Rebo Wekasan is not only a ritual to ward off evil, but also a dynamic and adaptive local tradition.